A comparative analysis of the sense of optimism and life satisfaction among judo and brasilian jiu jitsu fighters - Kanupriya Rawat; Ryszard Pujszo; Marta Wojdat; Magdalena Zając (Kazimierz Wielki University, 2022)
Background and Study Aim   The main aim of the study was to determine the level of optimism and life satisfaction among men of different ages who professionally or recreationally practice judo and Brazilian jiu-jitsu.   Material and Methods   The study involved 43 judo athletes, 43 Brazilian jiu-jitsu athletes (BJJ) and 42 persons in a control group (homogenously selected in terms of sex and age). The study used the SWLS scale to determine the satisfaction with life and the LOT-R test to determine the level of optimism. Descriptive parametric statistics were presented in order to show the analysed variables. Due to the number of subjects in groups, nonparametric statistics were used in the analysis - to analyse the differences, the Anova Kruskal-Wallis test; to analyse correlations between variables, the agglomerations method using Euclidean distances (single bond in space). In the analysis of the magnitude of the influence of variables on life satisfaction and optimism, parameter β was used - the significance of the parameter (p) was based on Wald's statistics.   Results   Analysis of intergroup differences for the judo, BJJ, and control groups revealed significant differences in education, social status, professional work, and health condition. The compared psychological variables - quality of life and life orientation in terms of standardised results did not reveal significant differences; however, the dichotomous division of the quality of life allowed indicating the distinctness of the compared groups. The analysis of multiple comparisons revealed that the differences only concerned the characteristics of the judo and the control groups, while the BJJ and the judo groups significantly differed in the quality and the length of their sports careers. Systems of characteristic features to explain the quality of life and life orientation were also searched for - the agglomerations method allowed indicating the distinctness of the BJJ and the judo groups in terms of the length of their sports careers. Based on the conducted logistic regression analysis, the likelihood of high or low quality of life and of life orientation and optimism in both groups of athletes has been identified, and differences consistent with previous observations have been indicated.   Conclusions   The subjects involved in combat sports significantly differ from those who do not practice sports in terms of education, social status, work situation and health assessment. The presence of high or low life satisfaction differentiates the compared groups.